Estimates of disclosure and victimization rates for fishery observers in the maritime workplace - Jeroue, Lacey; Faunce, Craig; Kingham, Andy; Smith, Jaclyn (Frontiers in Marine Science, 2025)
Seafarers working in remote ports and onboard fishing vessels often face isolated, high-risk environments, making them vulnerable to sexual harassment, intimidation, and assault. In the United States and other countries, scientists, called fishery observers, are required by the government to be deployed alongside fishing crews for extended periods to collect essential fisheries data and report potential fishing regulation violations they witness. Although many fishery observers who experience harassment submit official report statements, the true prevalence of the problem is unknown due to nondisclosure. This study uses anonymous responses from annual surveys distributed to North Pacific groundfish and halibut fishery observers to understand barriers to disclosure and estimate disclosure rates. By adjusting the annual counts of observers who submitted official harassment statements with these estimated disclosure rates, we provide the first estimates of the true number of victimized observers (prevalence) each year in a federal fisheries monitoring program in the United States. Model selection suggested that disclosure was influenced by the type of harassment experienced and not by observer demographics or employment year. Estimated disclosure rates (victimized observers who reported annually via official statement) were lowest for sexual harassment (0.18; 95% CI 0.11-0.29); higher for intimidation, coercion and hostile work environments (0.37; 95% CI 0.28-0.47); and highest for assault (0.57; 95% CI 0.41-0.73). Overall, 45% (95% CI 39-51%) of observers who experienced victimization disclosed harassment in a given year. We estimate that 22-38% of observers were victimized annually during the 2016-2022 study period, with rates of 24-60% for females and 12-24% for males. Victimization rates computed from raw survey summary statistics suffer from self-selection bias while rates derived solely from submission of official statements suffer from bias in underreporting. Supplementing official statements with estimates of disclosure rates from anonymous survey data provides a means of mitigating for these two forms of biases to obtain estimates of victimization untangled from fluctuations in reporting tendencies. When disclosure and victimization are teased apart, the effectiveness of risk reduction strategies can be better assessed over time.